2021
DOI: 10.1002/csc2.20527
|View full text |Cite
|
Sign up to set email alerts
|

Variability and trait‐specific accessions for grain yield and nutritional traits in germplasm of little millet (Panicum sumatrense Roth. Ex. Roem. & Schult.)

Abstract: Little millet (Panicum sumatrense Roth. Ex. Roem. & Schult.), a member of the grass family Poaceae, is native to India. It is nutritionally superior to major cereals, grows well on marginal lands, and can withstand drought and waterlogging conditions. Two-hundred diverse little millet landraces were characterized to assess variability for agronomic and nutritional traits and identify promising accessions. Highly significant variability was found for all the agronomic and grain nutrient traits. Accessions of ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Although millets are recognized as being naturally rich in iron, their nutrient composition varies with the type, variety, and growing conditions. Commonly used food composition tables while providing an overview of the nutrient composition do not include this detail ( 5 , 9 , 10 ). Presenting a single value for iron level in a type of millet can be misleading as iron levels can vary significantly among varieties.…”
Section: Introductionmentioning
confidence: 99%
“…Although millets are recognized as being naturally rich in iron, their nutrient composition varies with the type, variety, and growing conditions. Commonly used food composition tables while providing an overview of the nutrient composition do not include this detail ( 5 , 9 , 10 ). Presenting a single value for iron level in a type of millet can be misleading as iron levels can vary significantly among varieties.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, one can use XRF to discard the lines, segregate populations with low Fe and Zn, and validate all high Fe and Zn lines with ICP-OES method. Recently, Vetriventhan et al (2021) reported the use of ICP-OES method to estimate Fe, Zn, and Ca content in 200 diverse little millet landraces. Of the total number of accessions evaluated, approximately 80% of accessions revealed consistent protein and Zn content, whereas less consistency was observed for Fe (64%) and Ca (30%) content.…”
Section: Precision Phenotyping For Grain Micronutrient Contentmentioning
confidence: 99%
“…Hence, one can use XRF to discard the lines, segregate populations with low Fe and Zn, and validate all high Fe and Zn lines with ICP-OES method. Recently, Vetriventhan et al. (2021) reported the use of ICP-OES method to estimate Fe, Zn, and Ca content in 200 diverse little millet landraces.…”
Section: Precision Phenotyping For Grain Micronutrient Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Panicum sumatrense (Little millet) is one of the predominant yet lesser-studied, tetraploid species (2n = 4x = 36) of minor millets, essentially cultivated for its grain ( Gomez and Gupta, 2003 ; Das et al., 2020 ). The crop is loaded with nutrients such as dietary fiber, protein, and minerals like iron (Fe = 32.20 ppm) and zinc (Zn = 32.40 ppm) ( Girish et al., 2014 ; Vetriventhan et al., 2021 ) and performs exceptionally well under challenging environmental conditions and is invariably adapted to high temperature and moisture stress ( Ajithkumar and Panneerselvam, 2014 ). Yet, to date, the crop has been considered an ‘orphan’ and has never fallen under the umbrella of extensive research until recent years.…”
Section: Introductionmentioning
confidence: 99%